Black Polling Avoidance by Person Identification Using Biometrics - D.Catherine Rakkini1 , Pradeep.S. R , Deepthi.N , M. Ragavi Sudha B. E (International Journal of Emerging Trends in Science and Technology, 2017)
The objective of voting is to allow voters to exercise their right to express their choices regarding specific issues, pieces of legislation, citizen initiatives, constitutional amendments, recalls and/or to choose their government and political representatives. It has always been an onerous task for the election commission to conduct free and fair polls in our country, the largest democracy in the world. A lot of money have been spent on this to make sure that the election is rampage free. In order to provide in expensive solutions to the above, this project will be implemented with biometric system i.e. finger print scanning.